2015
DOI: 10.1093/ehjci/jev174
|View full text |Cite
|
Sign up to set email alerts
|

Device landing zone calcification and its impact on residual regurgitation after transcatheter aortic valve implantation with different devices

Abstract: Calcification of the device landing zone, particularly if located inferior to the annulus, was independently associated with residual AR after TAVI with all evaluated THV; however, the incidence of paravalvular leakage differed significantly between the devices implanted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 27 publications
5
46
0
1
Order By: Relevance
“…15 The present study demonstrated that excessive calcification of the native aortic valve was independently associated with significant PVR after TAVI. This was also demonstrated by Seiffert et al 16 in a recent study including 537 patients treated with different models of TAVI bioprostheses (SAPIEN XT, JenaValve, Symetis, CoreValve, and Engager). Larger AVC load, particularly at the level of the LVOT inferior to the annulus (coefficient 0.146, 95% CI 0.038 to 0.253, p ¼ 0.008), and type of bioprosthesis (CoreValve; coefficient 0.368, 95% CI 0.233 to 0.503, p <0.001) were independently associated with PVR after TAVI.…”
Section: Discussionsupporting
confidence: 68%
“…15 The present study demonstrated that excessive calcification of the native aortic valve was independently associated with significant PVR after TAVI. This was also demonstrated by Seiffert et al 16 in a recent study including 537 patients treated with different models of TAVI bioprostheses (SAPIEN XT, JenaValve, Symetis, CoreValve, and Engager). Larger AVC load, particularly at the level of the LVOT inferior to the annulus (coefficient 0.146, 95% CI 0.038 to 0.253, p ¼ 0.008), and type of bioprosthesis (CoreValve; coefficient 0.368, 95% CI 0.233 to 0.503, p <0.001) were independently associated with PVR after TAVI.…”
Section: Discussionsupporting
confidence: 68%
“…It was previously found to be associated with increased PVL or PD rates, and annulus injury only following BE-THV implantations. [7][8][9]11,12) Previous studies also demonstrated that there is reduced rates of PVL or PD following XT compared to CV TAVI. [4][5][6] Most of these previous studies included different grades of aortic valve calcification but did not evaluate association with DLZ calcification.…”
Section: Discussionmentioning
confidence: 99%
“…The upper LVOT region was defined as the cross-sectional region 2 mm inferior to the annular plane (Figure 1). 7,9,11,12) After excluding patients with the absence of up- per LVOT calcification (252 patients), previous bioprosthesis (45 patients), and patients with poor CT imaging quality (8 patients), a total of 174 patients were included in the final analysis. These patients were divided into two groups according to valve design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of calcium in the TAVI device landing zone, defined as a volume or Agatston units, is a predictor of residual PVL [60,61].…”
Section: Patient Screening and Qualification To Tavimentioning
confidence: 99%